Sweet sorghum and Miscanthus: Two potential dedicated bioenergy crops in China - Shi-wei HU; Lei-ming WU; Staffan Persson; Liang-cai PENG; Sheng-qiu FENG (Journal of Integrative Agriculture, 2017)
Among the potential non-food energy crops, the sugar-rich C4 grass sweet sorghum and the biomass-rich Miscanthus are increasingly considered as two leading candidates. Here, we outline the biological traits of these energy crops for large-scale production in China. We also review recent progress on understanding of plant cell wall composition and wall polymer features of both plant species from large populations that affect both biomass enzymatic digestibility and ethanol conversion rates under various pretreatment conditions. We finally propose genetic approaches to enhance biomass production, enzymatic digestibility and sugar-ethanol conversion efficiency of the energy crops.